Tea shoot production in relation to rainfall, solar radiation and temperature in Pagilaran tea estate, Batang=Produksi pucuk teh, hubungannya dengan curah hujan, panjang penyinaran sinar matahari dan suhu di kebun teh... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
Tea shoot production pattern in PT Pagilaran tea estate, Batang is studied in relation to rainfall, solar radiation and temperature. pagilaran tea estate is located at 700-1,500 m above the sea level, with temperature of 15-30 degrees C and ranging from 4,500 mm to 7000 mm per year. However the area is also characterized by up to three dry month for every three years.